GAMBARAN PENGETAHUAN IBUAKSEPTOR KB SUNTIK TENTANG GANGGUAN MENSTRUASI AKIBAT KONSTRASEPSI DEPO PROGESTIN ASETAT DI BPM MULYATIN,AMKeb, SKM SAMPIT TAHUN 2018 - alwita susanti (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2019)
ABSTRACT Background: Injection family planning acceptors still lack knowledge. Based on the preliminary study held on April 8, 2018 at Mulyatin Midwifery Practice, and direct interview to ten Depo Progesteron Acetate acceptors, seven women lacked knowledge on menstrual problems while three had enough knowledge on the matter. Objective: To understand the description of the knowledge of injection family planning acceptors on menstrual problems caused by Depo Progestin Acetate contraception at Mulyatin Midwifery Practice, in 2018. Methods: It is a Descriptive study, using Cross Sectional approach. Sample collection was done by means of Accidental Sampling with 42 respondents. The location of the study was Mulyatin Midwifery Practice in Sampit in 2018. Data analysis used was Univariat analysis. Result: From the study it was found that there were eight respondents (19.05%) with good knowledge, 31 respondents (73.81%) with enough knowledge, and three respondents (7.14%) with little knowledge. Conclusion: Based on the study, 73.81% of respondents had enough knowledge on menstrual problems caused by Depo Progestin Acetate contraception at Mulyatin Midwifery Practice, in 2018. Key Words: Knowledge, Age, Education, Occupation, Information sources of family planning acceptors on menstrual problems caused by Depo Progestin Acetate Contraception.